Diagnosis of Helicobacter pylori infection: Current options and developments - Wang, Yao-Kuang (World journal of gastroenterology : WJG, 2015)
Accurate diagnosis of Helicobacter pylori(H. pylori) infection is a crucial part in the effective management of many gastroduodenal diseases. Several invasive and non-invasive diagnostic tests are available for the detection of H. pylori and each test has its usefulness and limitations in different clinical situations. Although none can be considered as a single gold standard in clinical practice,several techniques have been developed to give the more reliable results. Invasive tests are performed via endoscopic biopsy specimens and these tests include histology,culture,rapid urease test as well as molecular methods. Developments of endoscopic equipment also contribute to the real-time diagnosis of H. pylori during endoscopy. Urea breathingtest and stool antigen test are most widely used noninvasive tests,whereas serology is useful in screening and epidemiological studies. Molecular methods have been used in variable specimens other than gastric mucosa. More than detection of H. pylori infection,several tests are introduced into the evaluation of virulence factors and antibiotic sensitivity of H. pylori,as well as screening precancerous lesions and gastric cancer. The aim of this article is to review the current options and novel developments of diagnostic tests and their applications in different clinical conditions or for specific purposes.